Wildfire risk modeling - Oliveira, Sandra (2021)
Wildfires occur worldwide and affect different territories in diverse ways. New challenges in wildfire management are emerging, fueled by climatic, land cover, and sociodemographic changes, fostering wildfire science to respond with advanced and inclusive approaches. Supported by technological improvements, wildfire risk modeling is earning relevance in several wildfire phases, covering prevention, suppression, and recovery, and encouraging the development of different products and tools. Most wildfire risk approaches reflect a broad conceptual framework that includes different but interconnected components, which can also be analyzed separately, such as likelihood, hazard, exposure, vulnerability, and coping capacity. This article presents a concise and nonexhaustive review of the methods and approaches applied to model wildfire risk and its key components, in particular since 2018, and how they can contribute to wildfire management.